Perancangan Website TMLESS Studio dengan Metode Design Thinking - Yohanes Tennary Rinto Pradhana; Joko Purwadi; Raden Gunawan Santosa (Jurnal Terapan Teknologi Informasi, 2025)
TMLESS Studio is an entertainment company based in Yogyakarta, Indonesia, which is engaged in content creation ranging from films and music videos to series and documentation. The documentation service offerings provided by TMLESS Studio are still carried out by introducing themselves directly to prospective customers or with the help of old customers who recommend their services to prospective customers. TMLESS Studio has tried to use social media as a marketing medium, but this is still considered to have no impact on service sales. The solution that will be carried out to help solve this problem is to design a website to display complete information on TMLESS Studio's work and documentation service offerings in one area. The TMLESS Studio website will be designed using the Design Thinking method which includes 5 stages, namely empathize, define, ideate, prototype, and test. At the test stage, testing will be carried out using the Single Ease Question (SEQ) using the help of Google Sites and Google Form to find out whether the tested website can overcome the initial problem. The results of the SEQ respondent data average test show that the website being tested is in the very easy category (average = 6.19). The results of the average test of Tasks 5, 6, 7, and 8 regarding information on works and services offered by TMLESS Studio are in the very easy category. The results of this test show that the application of the stages of the Design Thinking method and the implementation of SEQ in the design of the TMLESS Studio website being tested has succeeded in overcoming the problems and can be used as a permanent TMLESS Studio website.